How Fantasy Speaks to Adolescent Readers - Julie Smit (University of Oklahoma Libraries, 2020)
Many genres of fictional novels are considered groundbreaking for complex plots and psychologically interesting characters. Little attention has been focused on how fantasy can be groundbreaking. This exploratory case study centers on how the five-novel series Percy Jackson & the Olympians, and its five-part sequel The Heroes of Olympus, speaks to a reading community of eighth grade female adolescent readers. This study traces the development of social inquiries of gender inequality, heroism and imperfection, and good and evil from these readers' interactions with characters and events in the world of Percy Jackson.